Murru Minya–informing the development of practical recommendations to support ethical conduct in Aboriginal and Torres Strait Islander health research: a protocol for a national mixed-methods study. Issue 2 (10th February 2023) - McGuffog, Romany; Chamberlain, Catherine; Hughes, Jaqui; Kong, Kelvin; Wenitong, Mark; Bryant, Jamie; Brown, Alex; Eades, Sandra J; Griffiths, Kalinda E; Collis, Felicity; Hobden, Breanne; O'Mara, Peter; et al.
Abstract : Introduction: Conducting ethical and high-quality health research is crucial for informing public health policy and service delivery to reduce the high and inequitable burden of disease experienced by Aboriginal and Torres Strait Islander people. Ethical guidelines and principles specifically for health research with Aboriginal and Torres Strait Islander people have been developed for use since 1987. However, there has been limited examination of how these are being applied to the conduct of research. Methods and analysis: Murru Minya will be a large-scale national study to examine the implementation of ethical processes in Aboriginal and Torres Strait Islander health research. A mixed-methods design will be used in four baarra (steps). The first three baarra will collect knowledge, experiences and wisdom from three key groups: Aboriginal and Torres Strait Islander communities, research academics, and Human Research Ethics Committees using online surveys, yarning, and semistructured interviews. This knowledge will inform the final baarra of developing a set of practical recommendations to support ethical conduct in Aboriginal and Torres Strait Islander health research into the future. Ethics and dissemination: Ethical approval for this research project has been granted by National, State and Territory Human Research Ethics Committees. This research has been developed in collaboration with Aboriginal and Torres Strait Islander researchers, Aboriginal Community Controlled Health Organisation representatives, Aboriginal community members, the National Health Leadership Forum, and Aboriginal and Torres Strait Islander research team. The knowledge translation plan will be integrated and revised throughout the project as partnerships and engagement with Aboriginal and Torres Strait Islander communities continue. All findings will be shared with peak Aboriginal research bodies and Aboriginal and Torres Strait Islander communities in ways that are meaningful to them.